EVALUATION OF A TALENT MANAGEMENT SYSTEM - Koyana, Zimasa Sibongile Shadinah (My University, 2011)
The combination of highly mobile talent workers and the turbulent economy places more responsibility on organisations to be proactive in managing their human capital through an effective talent management system. The ability to identify, recruit, develop and retain the best staff can create continuous value for stakeholders and can give an organisation a competitive advantage. Thus every organisation needs to understand talent workers in terms of what they think, what they want, what they are willing to contribute, and what they expect in return. The purpose of this research was to identify the elements of a talent management system, and factors that contribute to its effectiveness through an investigation of a system in place at a South African organisation within the food and beverage industry. A qualitative research methodology was used and this allowed the researcher to conduct unstructured interviews with both management and talent workers. The researcher was able to interact with them in their natural setting so as make sense of and interpret phenomena in terms of the meaning people bring to the phenomena. The data was subjected to content analysis. Factors which emerged as important for talent workers were compared with factors that managers thought were most effective in identifying, recruiting, developing and retaining critical talent. These results were cross checked against other qualitative data sources such policies and best practice. The interpretation of results revealed that this organisation‘s talent management system has the following elements: identifying talent workers from within, identifying talent workers from outside, managing and developing talent workers, and retaining talent workers. A combination of the following factors: talent friendly organisation, communication, career advancement opportunities, strong presence in the market place, an A-list reward system, clearly set goals, effective performance management, training, visible and caring leadership, high performance teams and results-driven culture lead to the effectiveness of this organisation‘s talent management system
MBA - WBS
Keywords: Talent management